2008
DOI: 10.1080/13552600802267098
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sexual recidivism as a function of age and actuarial risk

Abstract: The study of risk for sexual recidivism has undergone substantial development in recent years. The foundation for advances in this area has been the use of actuarial measures to identify subgroups of offenders with different observed rates of sexual re-offending over time. An unresolved issue within this research area has been the moderating function of age in the assessment of risk. The current study examined sexual re-offending as a function of age and actuarial risk in a large sample of sexual offenders rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
3
17
0
3
Order By: Relevance
“…Hanson [10] 3.425 Sexualstraftäter über einen Zeitraum von fünf Jahren und fand einen Abfall der Rückfallraten erst ab einem Alter von rund 40 Jahren mit durchschnittlich 15% einschlä-giger Rückfälle der jüngeren Täter bis zu nur mehr rund zwei Prozent bei den über 60jährigen. Skelton und Vess [25] beobachteten erst ab einem Alter von 50 Jahren einen signifikanten Rückgang der einschlägigen Rück-fallquote; hier wurden rund drei Prozent der über 60-Jährigen im Vergleich zu gut neun Prozent der Gesamtstichprobe einschlägig rückfällig. Trotz der konstanten Erkenntnis, dass die ältesten Altersgruppen stets die geringste einschlägige Rückfallrate aufweisen, scheint insofern die Frage nach der genauen Altersschwelle, ab der die Risiken abnehmen, derzeit noch nicht abschließend geklärt.…”
Section: Offending Characteristics Risk Of Recidivism and Predictionunclassified
See 2 more Smart Citations
“…Hanson [10] 3.425 Sexualstraftäter über einen Zeitraum von fünf Jahren und fand einen Abfall der Rückfallraten erst ab einem Alter von rund 40 Jahren mit durchschnittlich 15% einschlä-giger Rückfälle der jüngeren Täter bis zu nur mehr rund zwei Prozent bei den über 60jährigen. Skelton und Vess [25] beobachteten erst ab einem Alter von 50 Jahren einen signifikanten Rückgang der einschlägigen Rück-fallquote; hier wurden rund drei Prozent der über 60-Jährigen im Vergleich zu gut neun Prozent der Gesamtstichprobe einschlägig rückfällig. Trotz der konstanten Erkenntnis, dass die ältesten Altersgruppen stets die geringste einschlägige Rückfallrate aufweisen, scheint insofern die Frage nach der genauen Altersschwelle, ab der die Risiken abnehmen, derzeit noch nicht abschließend geklärt.…”
Section: Offending Characteristics Risk Of Recidivism and Predictionunclassified
“…17,22], wo man bei den über 60-jährigen Vergewaltigern keinen einschlägi-gen Rückfall fand, aber auch bei den Missbrauchstätern dieser Altersgruppe nunmehr einen signifikanten Rück-gang im Vergleich zu den jüngeren Tätern. Die Ergebnisse deuten insofern auf einen linearen Trend nachlassender Rückfallrisiken für die Tätergruppe der Vergewaltiger zumindest ab dem mittleren Erwachsenenalter und auf einen demgegenüber deutlich verzögerten Beginn altersbedingt nachlassender Risiken bei den Missbrauchstätern hin [10,25,26].…”
Section: Offending Characteristics Risk Of Recidivism and Predictionunclassified
See 1 more Smart Citation
“…Another factor is age. Research has consistently shown that risk of sexual re‐offending decreases substantially with age, especially in offenders over the age of 50 (Barbaree, Blanchard, & Langton, ; Doren, ; Hanson, ; Skelton & Vess, ; Wollert, Cramer, Waggoner, Skelton, & Vess, ). However, there are a few individuals who have been observed to continue offending after the age of 70.…”
Section: Discussionmentioning
confidence: 99%
“…It is only with this information that users of a risk-assessment report will have general sense of approximately where a particular individual falls in the overall distribution of offenders. In the case of measures such as the Automated Sexual Recidivism Scale (ASRS) developed for use in New Zealand (Skelton, Riley, Wales, & Vess, 2006;Skelton & Vess, 2008; in press), it would be useful to know the portion of the overall samples that fall within each designated risk category as well as the corresponding reoffense rates.…”
mentioning
confidence: 99%